SISTEM PENJAMINAN MUTU INTERNAL MADRASAH BERBASIS NILAI-NILAI PESANTREN DI MA DARUL HUDA MAYAK - Khamilatul Husna; Muhammad Thoyyib (Excelencia: Journal of Islamic Education & Management, 2021)
The government implements a quality assurance system in response to various Indonesian quality problems. Madrasah like MA Darul Huda as an educational institution that focuses on general science and religious knowledge in which preserving the values ​​of pesantren needs to implement quality assurance system internally. This paper aims to study the internal quality assurance system of madrasah starting from setting quality standards, quality mapping, quality fulfillment planning, quality fulfillment, and evaluating quality fulfillment based on pesantren values embedded in all madrasa components. The study was conducted at MA Darul Huda Mayak Ponorogo. This study adopts a qualitative approach through case study research. In implementing quality assurance, MA Darul Huda follows government policies by referring to the National Education Standards and all quality policies ranging from quality standards to the implementation of programs and evaluation of quality compliance in accordance with the vision and mission and conditions of the madrasa. The values of pesantren that are embedded in madrasah stakeholders influence the running of quality assurance